1995
DOI: 10.1136/adc.72.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing respiratory syncytial virus by nasal lavage.

Abstract: Nasal lavage was compared with nasopharyngeal aspiration for diagnosis of respiratory syncytial virus infection. Nasal lavage and nasopharyngeal aspiration were performed on 50 occasions in 32 infants (median age 5 6 months) with acute viral wheezing. Compared with nasopharyngeal aspiration, nasal lavage had a positive predictive value of 95-6% and negative predictive value of 92.5%. These comparable results and lack of adverse effects make nasal lavage the preferred method. (Arch Dis Child 1995; 72: 58- Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
4
0
3
Order By: Relevance
“…A major strength of this study was that the prevalence of respiratory virus was assessed using two sampling techniques: nasal lavage and mucosal scrapes from the inferior turbinate. Although respiratory samples for detection of respiratory viruses are generally collected by nasopharyngeal swabs or nasopharyngeal aspirate in adults (31), nasal lavage fluid and scraped inferior turbinate epithelial cells have been used to detect respiratory virus in upper respiratory tract (27,30,(32)(33)(34). This multitechnique approach to the detection of respiratory viruses improved the sensitivity, and the results of this study confirmed the prevalence of respiratory viruses in the nasal cavity of CRS patients.…”
Section: Discussionsupporting
confidence: 58%
“…A major strength of this study was that the prevalence of respiratory virus was assessed using two sampling techniques: nasal lavage and mucosal scrapes from the inferior turbinate. Although respiratory samples for detection of respiratory viruses are generally collected by nasopharyngeal swabs or nasopharyngeal aspirate in adults (31), nasal lavage fluid and scraped inferior turbinate epithelial cells have been used to detect respiratory virus in upper respiratory tract (27,30,(32)(33)(34). This multitechnique approach to the detection of respiratory viruses improved the sensitivity, and the results of this study confirmed the prevalence of respiratory viruses in the nasal cavity of CRS patients.…”
Section: Discussionsupporting
confidence: 58%
“…Nasal lavage can be substituted for nasopharyngeal aspirates. 59 The results of viral detection tests are particularly useful for cohorting infected children during outbreaks and for epidemiological purposes.…”
Section: Viral Pneumoniamentioning
confidence: 99%
“…Previous studies have demonstrated nasal washing to be operationally useful in the hospital(1,4) and community(5,6) settings, and have shown high viral titre yield(2,7). The procedure of nasal lavage, similar to NWs but with mechanical aspiration, has been shown to compare well with NPA in RSV diagnosis efficiency (8). Taken together with simpler equipment requirements, these facts suggest nasal washing methods may have considerable merit for use in minimal resource, and home, settings.…”
Section: Discussionmentioning
confidence: 84%